Spirit & Vision : aboriginal art - Sammlung Essl Kunst der Gegenwart, Klosterneuburg (Wien) (Klosterneuburg (Wien) : Sammlung Essl Kunst der Gegenwart Klosterneuburg (Wien), 2004)
Ah Kee, Vernon ; An.Gunguna, Jimmy ; Andrew, Brook ; Apuatimi, Jean-Baptiste ; Bayamarrawunga, Laurie ; Bedford, Paddy ; Bell, Richard ; Binyinyiwuy ; Black, Carol ; Brian, Charlie ; Brown, May ; Butler, Charlie ; Butler, Sammy ; Carnegie, Aubrey ; Davidson, Jason ; Deacon, Destiny ; Dhamarrandji, Gunguyuma ; Doneghan, Jimmy ; Dowling, Julie ; Downs, Jarinyanu David ; Duncan, Billy ; Durrng, Micky ; Foley, Fiona ; Forbes, Dennis ; Foster, Wilton ; Fraser, Jenny ; Fraser, Virginia ; Gordon, Anne-Marie ; Greene, Gracie ; Gudapi, Willie ; Gunjarrwanga, Melba ; Helicopter ; Iyuna, James ; Jackson, Reggie ; Jackson, Ron ; Jagamara, Michael Nelson ; Jampijinpa, Kaapa Mpetyane ; Jangala, Abie ; Johns, Ned ; Kaline, Tammy ; Karrkarrhba, Hamish ; Kerinauia, Dymphna ; Kerinauia, Raelene ; Kngwarreye, Emily Kame ; Kubarkku, Mick ; Laidlaw, Mrs ; Lane, Elaine ; Lewis, Joe ; Lindjuwanga, Kay ; Loomoo, Lucy ; Mathaman, Marika ; Mawurndjul, John ; McKenzie, Queenie Nakarra ; Milner, Boxer ; Milpurrurru, George ; Mitchell, Walya ; Mudjidell, Brian ; Munkara, Therese Ann ; Nabulumo, Namarinjmak Paul ; Namirrkki, Ivan ; Namok, Rosella ; Nanala, Dulcie ; Nanninurra, Nancy ; Napurrula, Walangkura Reid ; Nawilil, Jack ; Ngalakurn, Jimmy ; Noonju, Nancy ; Nungurrayi, Pantjiya ; Nyukuti, Jim ; Pascoe, Jack ; Pascoe Malparringa, Matilda ; Petyarre, Gloria ; Petyarre, Kathleen ; Petyarre, Violet ; Puantulura, Natalie ; Puruntatameri, Maree ; Puruntatameri, Matthew Freddy ; Pwerle, Minnie ; R E A ; Riley, Michael ; Shepherd, Bob ; Siwes, Darren ; Steele, Tommy Gondorra ; Thomas, Billy ; Thomas, Rover Julama ; Thompson, Christian ; Tjakamarra, Anatjari ; Tjampitjinpa, Old Walter ; Tjampitjinpa, Ronnie ; Tjangala, Uta Uta ; Tjapaltjarri, Clifford Possum ; Tjapaltjarri, Mick Namarari ; etc.
bibliog. p. 264-265
Duits, Engels
Exhibition "Spirit & Vision : Aboriginal Art", Sammlung Essl Kunst der Gegenwart Klosterneuburg (Wien), 02.04.2004 - 29.08.2004
boek